Highly active antiretroviral therapy in Brazil: the challenge of universal access in a context of social inequality La terapia antirretrovírica de gran actividad en el Brasil: el reto del acceso para todos en un contexto de desigualdad social - Mariana A. Hacker (Revista Panamericana de Salud Pública, 2004)
OBJECTIVE: To investigate trends in AIDS mortality and incidence in Brazil over the period of 1984 to 2000 and to assess the impact of the introduction of universal access to highly active antiretroviral therapy (HAART) in the country in 1996. METHODS: Data from the Brazilian disease notification system and the national mortality information system were used to calculate annual region-specific and sex-specific AIDS incidence and mortality rates. We also calculated sex- and region-specific ratios of the number of AIDS deaths in one year to the number of AIDS cases notified two years earlier. RESULTS: AIDS mortality rates for both men and women and in all five of the geographic regions of Brazil declined following introduction of HAART, despite continued growth in AIDS incidence. The ratio of the number of AIDS deaths in one year to the number of AIDS cases notified two years earlier for men equalized rapidly with the ratio for women following introduction of HAART. More recently, AIDS incidence declined for both sexes and in most of the regions of Brazil. CONCLUSIONS: Despite Brazil's resource limitations and disparities in wealth between men and women and among the country's regions, the introduction of universal access to HAART in Brazil has helped achieve impressive declines in AIDS mortality, and it may also be contributing to declines in AIDS incidence. OBJETIVO: Investigar las tendencias que han mostrado la mortalidad y la incidencia del sida en el Brasil durante el período de 1984 a 2000 y evaluar el efecto de la introducción en el país en 1996 de la terapia antirretrovírica de gran actividad (TAGA) accesible a toda la población. MÉTODOS: Se usaron datos procedentes del sistema de notificación de enfermedades del Brasil y del sistema nacional de información sobre mortalidad para calcular las tasas de incidencia y de mortalidad por sida en cada región del país y según el sexo. También calculamos para cada región y según el sexo, las razones dadas por el número de muertes por sida en un año contra el número de casos de sida notificados dos años antes. RESULTADOS: Las tasas de mortalidad en las cinco regiones del Brasil descendieron tanto en hombres como en mujeres después de adoptarse la TAGA, a pesar de que la incidencia de sida siguió aumentando. La razón del número de muertes por sida en un año al número de casos de sida notificados dos años antes llegó a emparejarse muy pronto en hombres y mujeres después de la introducción de la TAGA. En época más reciente, la incidencia de sida se ha reducido en ambos sexos en la mayoría de las regiones del Brasil. CONCLUSIONES: A pesar de los limitados recursos que posee el Brasil y de las disparidades económicas observadas entre hombres y mujeres en las distintas regiones del país, la introducción de la TAGA accesible a toda la población ha ayudado a lograr un descenso muy notable de la mortalidad por sida y podría estar contribuyendo a reducir la incidencia de la enfermedad.